2022
DOI: 10.3390/nu14020381
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Predictive Value of Evidence-Based Referral Criteria to Support Healthy Gestational Weight Gain among an Australian Pregnancy Cohort

Abstract: Globally, there has been a renewed focus on addressing gestational weight gain (GWG). In Australia, the Department of Health pregnancy care guidelines recommend women be offered routine weighing and receive brief nutritional and physical activity support during antenatal care visits. Women gaining weight outside the Institute of Medicine (IOM)’s weight gain reference values are further recommended to be referred to a dietitian. However, professional and organizational barriers, including an absence of weight g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Lower referrals may also reflect a lower prioritisation of GWG as a referring health issue, and a lack of public dietetic service capacity to provide timely referrals to address maternal health as found in other Australian research [ 37 ]. It has been suggested that care aspects like referring to other care services require more time and follow-through [ 36 ], better care provider education and guidance, and different organisational structures and more service capacity [ 37 , 38 ]. Further research should investigate both pregnant women’s acceptability of, and antenatal care providers’ barriers to, offering GWG referrals to maximise acceptance and engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Lower referrals may also reflect a lower prioritisation of GWG as a referring health issue, and a lack of public dietetic service capacity to provide timely referrals to address maternal health as found in other Australian research [ 37 ]. It has been suggested that care aspects like referring to other care services require more time and follow-through [ 36 ], better care provider education and guidance, and different organisational structures and more service capacity [ 37 , 38 ]. Further research should investigate both pregnant women’s acceptability of, and antenatal care providers’ barriers to, offering GWG referrals to maximise acceptance and engagement.…”
Section: Discussionmentioning
confidence: 99%